Numerical and experimental investigation of utilizing the porous media model for windbreaks CFD simulation. (February 2021) - Mahgoub, Ahmed Osama; Ghani, Saud
Highlights: Empirical formulae to estimate the porous media model coefficients are proposed. Comparison with exact geometry CFD yielded RMSE value of 10.5% for the velocity. Comparison with exact geometry CFD yielded RMSE value of 12% for the pressure. Proposed formulae are valid for windbreaks with a porosity ratio between 0.25–0.6. Abstract: Windbreaks such as vegetation barriers, fences, and buildings' perforated facades are used in various environmental and wind mitigation applications. Numerical simulation of the airflow through windbreaks is challenging as modeling of the exact geometry needs large computational power. The computational cost can be reduced by modeling the windbreaks using the porous media model. The computational fluid dynamics (CFD) model uses empirical coefficients that need to be determined experimentally. This research develops empirical formulae to determine the needed viscous and inertial loss coefficients as a function of porosity for perforated windbreaks. Particle image velocimetry (PIV) experiments and pressure measurements were performed in a wind tunnel for scaled windbreaks models of porosity ratios ranging from 0.25 to 0.6. CFD simulations were carried out for the exact geometry and for the approximated numerical model. The CFD results of both models were compared against the experimental results. Hence, a correlation between the windbreaks porosity and the needed coefficients to utilize the CFD porous media model was obtained. Compared to exact geometry CFD results, the average velocity and pressure drop values obtained from the porous media model yielded an average error of 10.5% and 12%, respectively.